From the addiction rehabilitation program to the return to work: results of an employment and social intervention among young adults with substance dependence - Fiabane, Elena; Ferraris, Eleonora; Ranalletti, Paola; Conti, Debora; Giorgi, Ines; Ottonello, Marcella; Argentero, Piergiorgio (La Medicina del Lavoro, 2016)
Introduction: Substance dependence problems are considered to be a relevant issue for a large proportion of the working population and represent a huge health and occupational cost. However, few studies have examined the return to work after addiction problems. Aims: This exploratory follow-up study aims to evaluate the return to work, in terms of employment outcomes, perceived work environment and physical and mental health of patients who have completed an addiction rehabilitation program and an employment and social intervention. Methods: The sample includes 51 participants with a baseline diagnosis of substance abuse disorder who have completed a rehabilitation and a social-occupational intervention. Patients were assessed by means of self-report questionnaires referring to perceptions of the work environment, individual characteristics and mental and physical health. Results: The results show that the majority of the sample (88.2%) is employed at follow-up and refers positive perceptions about the psychosocial work environment, the mental and physical health and the stabilization of the change. The factors that significantly influence job satisfaction are work ability (p=0.02), work engagement (p=0.04) and absence of desire (p=0.05). Conclusions: The present study shows that many patients some years after the rehabilitation program have kept their job with positive levels of individual and organizational well-being. Work is not perceived as a source of stress but it represents a protective factor for health, personal identity and social integration.